Nurses' knowledge and practice of blood-borne pathogens and infection control measures in selected Beni-Suef Hospitals Egypt. Issue 3 (September 2016) - Arafa, Ahmed E.; Mohamed, Amel A.; Anwar, Manal M.
Abstract : Background and purpose: Blood-borne pathogens (BBP) [hepatitis B virus (HBV), hepatitis C virus (HCV), and HIV] pose a considerable infectious risk for nurses, resulting in unwanted health outcomes and psychological stress. Aim of the work: This study aimed to assess the knowledge and practices of nurses and define administrative roles regarding in BBP and infection control (IC) measures in selected Beni-Suef Hospitals. Participants and methods: A cross-sectional study was carried out from December 2014 to January 2015 using a self-administered questionnaire. It was distributed to 400 nurses working in the Health Insurance Organization, Beni-Suef University/general, Nasser Center, and Bebba Hospitals, with a response rate of 77.5% (310/400). Results: The overall mean scores of knowledge, practice, and role of administration of respondent's nurses (out of 15 points, each) were 7.71±3.15, 9.14±2.47, and 7.03±3.58, respectively. Assessment of knowledge and practice showed that 93.5, 80.3, and 65.8% of nurses were aware that HIV, HBV, and HCV is a BBP, respectively. Autoclave as the best sterilization method for equipment was reported by greater than 50% of the nurses. Urban locality of the healthcare facility and lectures provided to the nursing staff were significantly related to better practice. However, 14.8% of nurses reported a needle-stick injury during the last 6 months and only 53.5% of nurses were vaccinated against HBV. Conclusion and recommendations: Both the knowledge and the practice of Beni-Suef Hospitals' nurses against BBP and IC standards were fair. The administration score was the only independent determinant for practice. Healthcare facilities should focus on increasing nurses' awareness for strict adherence to IC standards, and implement training and preventive programs to minimize the risk of needle-stick injuries. All nurses should be vaccinated against HBV.